PRESCRIPTION ANALYSIS: AN INVESTIGATION ON PRESCRIPTION LEGALITY IN THE PHARMACIES OF KOTAMADYA YOGYAKARTA - Rahmawati, Fita; Oetari, R.A. (INDONESIAN JOURNAL OF PHARMACY, 2002)
A research has been carried out to identify whether prescriptions received in pharmacies at Yogyakarta district fulfilled the legality as the regulation concern. This included an investigation on prescription hand-writing, part of a prescription which has a potential to bring about a medication error due to misinterpretation.The study was conducted by collecting prescription samples, randomly picked-up (ï¡=5% and d=3%), from each of 12 pharmacies. Furthermore, other supporting data, such as questioner and interview, were also collected from 29 pharmacies involving 83 respondents (24 pharmacists and 59 technician assistants). Data were then analyzed descriptively.The result showed that prescriptions fulfilled the regulation was approximately 39.8%. The absences of sign or license number of prescriber, the date of prescription were only examples of the cause. Hand-writing of the prescriber was sometime so bad that causing difficulty to interpret especially name of medicine, dose, usage or administration, uncommon abbreviation, hence increasing the risks of medication error to happen.Key word: prescription, legality aspect of prescription, medication error